Efek Anti-Inflamasi Tanaman Avicennia : Kajian Sistematik - Dinanti, Fathia Kesuma; Madusari, Benny Diah; Hernanda, Ary Setya (Fakultas Kedokteran Universitas Trisakti, 2025)
Avicennia, commonly known as mangrove plants, has been traditionally used to treat various diseases, including cancer, malaria, asthma, rheumatism, and ulcers. This genus possesses a range of unique secondary metabolites, belonging to various classes, which play a crucial role in numerous pharmacological activities, including the regulation of inflammation. Although many research articles have been published on the pharmacological properties of different species within this genus, no systematic review is yet available regarding their ethnomedicinal uses in the inflammatory process. This systematic review critically discusses studies on Avicennia species that exhibit anti-inflammatory effects, providing insights and guidance for future research on the plants as potential sources of new dietary supplements or medicinal agents. A literature search was conducted using internet databases such as PubMed, Scopus, Science Direct, and PubPharm, combining keywords like “Avicennia,” “inflammation,” and other related terms, following the PRISMA 2020 guidelines. Research articles were included if they were experimental (in vitro and in vivo) studies on the anti-inflammatory effects of Avicennia species and published in either Bahasa or English between 2012 and 2024. Ten studies on the anti-inflammatory effects of Avicennia species were selected. The five species of the genus Avicennia examined in these studies are A. alba, A. marina, A. schaueriana, A. officinalis, and A. rumphiana. The anti-inflammatory effects of Avicennia were demonstrated by the inhibition of inflammatory cytokine production, nitric oxide production, and inflammation in animal models. Additionally, the secondary metabolites and antioxidant effects of Avicennia species are reported in the selected articles. The phytochemicals of several Avicennia species have been shown to exhibit strong anti-inflammatory effects. Further preclinical studies, including toxicity and pharmacokinetic assessments, are necessary before they can be considered for clinical trials. The genus Avicennia has great potential to be developed into medicinal agents for diseases related to inflammation.